Características de la dieta en niños de 2 a 5 años, según la recepción de programas alimentarios en el hogar, en Argentina. - Acosta, Laura Débora (2014)
Objective: Analyzing the characteristics of the diet in Argentinian children aged 2 to 5, who received alimentary interventions at home during 2005. Methods: We analyzed the National Survey of Nutrition and Health (ennys). The ennys had a probabilistic sampling, stratified by conglomerates. n = 7046. The Propensity Score Matching (pms) methodology was used to constitute comparable groups of children who received and did not receive alimentary interventions at home. We analyzed the consumption of macro and micronutrients, energy, energy ratio assigned to each meal time and food groups. Results and Conclusions: We observed a lower consumption of energy and calcium and a higher proportion of energy from cereals in children that received alimentary intervention at home. This would show that children that receive alimentary programs do not present a better quality of their diets.